2012
DOI: 10.1534/g3.112.004150
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics ofPhytophthora infestansin the Netherlands Reveals Expansion and Spread of Dominant Clonal Lineages and Virulence in Sexual Offspring

Abstract: For a comprehensive survey of the structure and dynamics of the Dutch Phytophthora infestans population, 652 P. infestans isolates were collected from commercial potato fields in the Netherlands during the 10-year period 2000–2009. Genotyping was performed using 12 highly informative microsatellite markers and mitochondrial haplotypes. In addition, for each isolate, the mating type was determined. STRUCTURE analysis grouped the 322 identified genotypes in three clusters. Cluster 1 consists of a single clonal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 45 publications
3
71
0
1
Order By: Relevance
“…The genotyping data and isolate information can be found in Li et al . (). In addition the Shannon index and the evenness were calculated using the frequency data in Nicaragua reported by Blandón‐Díaz ().…”
Section: Methodsmentioning
confidence: 97%
“…The genotyping data and isolate information can be found in Li et al . (). In addition the Shannon index and the evenness were calculated using the frequency data in Nicaragua reported by Blandón‐Díaz ().…”
Section: Methodsmentioning
confidence: 97%
“…A recent example is the use of Rpi-blb1 against potato late blight (Phytophthora infestans), which was effective against all known races of P. infestans (124,139). Virulence to Rpi-blb1 has now been discovered in P. infestans from Mexico (31) and field samples in the Netherlands (88). Although Rpi-blb1 is still effective against most isolates and is being used in potato breeding (88), its durability depends on the cost of virulence.…”
Section: Rare Virulencementioning
confidence: 99%
“…Virulence to Rpi-blb1 has now been discovered in P. infestans from Mexico (31) and field samples in the Netherlands (88). Although Rpi-blb1 is still effective against most isolates and is being used in potato breeding (88), its durability depends on the cost of virulence. These coevolutionary predictions relate to a GFG system in which there is variation in the pathogen.…”
Section: Rare Virulencementioning
confidence: 99%
“…This allows for genetic recombination via sexual reproduction followed by rapid proliferation of the fittest individuals via asexual reproduction and dispersal via airborne sporangia or movement on infected plant tissue. The resulting clonal lineages, which are comprised of clonal descendants of one unique individual, then dominate a geographic region until a more fit individual displaces them [6,7]. In the United States, where sexual reproduction is not common but has been indirectly observed twice [8,9], novel-genotypes are presumed to emerge through migration [1012].…”
Section: Introductionmentioning
confidence: 99%
“…The 12 microsatellite markers currently used to genotype isolates of P . infestans have sufficient resolution to distinguish clonal lineages, and have also been used to investigate diversity within lineages [6,14,27]. Several studies have identified phenotypic variability among asexual P .…”
Section: Introductionmentioning
confidence: 99%